Urgent issues and prospects in reforming interrogation practices in the United States and Canada. (19th July 2020) - Snook, Brent; Barron, Todd; Fallon, Laura; Kassin, Saul M.; Kleinman, Steven; Leo, Richard A.; Meissner, Christian A.; Morello, Lorca; Nirider, Laura H.; Redlich, Allison D.; Trainum, James L.
Abstract : The current article presents a series of commentaries on urgent issues and prospects in reforming interrogation practices in Canada and the United States. Researchers and practitioners, who have devoted much of their careers to the field of police and intelligence interrogations, were asked to provide their insights on an area of interrogation research that they believe requires immediate attention. The submitted independent commentaries covered a variety of topics – from police recruitment, interrogation training, use of proper interrogation practices, and the treatment of confession evidence in court. Common concerns from the contributions pertained to the lag between scientific knowledge on interrogations and the application of such knowledge in the justice system, and the glaring disparity between the treatment of similar issues in the interrogation context versus other criminal justice contexts. A primary intent of this collection of commentaries is to serve as a resource pointing researchers in the direction of the fundamental areas that require immediate consideration and encouraging them to simultaneously pursue solutions to the overarching concerns that emerged from this project.